Effect of sleep-high/train-low on performance and well-being in well-trained triathletes - Dehnert, C.; Peterle, C.; Lormes, W.; Liu, Y.; Menold, E.; Baur, S.; Hutler, M.; Boning, D.; Gabriel, H.; Gomez-Islinger, R.; Lehmann, M.; Steinacker, J. M. (Medicine & Science in Sports & Exercise, 1997)
The effects of live-high/train-low on performance and well-being were analyzed. Physiological parameters were also monitored. Well-trained triathletes (N = 21) performed the same training schedule for two weeks. Two groups were formed with one group remaining at altitude (>1800 m; N = 11) for at least 12 hours per day, while both trained and one group (N = 10) lived at 800 m. The live-high group demonstrated higher hematocrits, less complaints, and better wellness at the end of the two-week period than the live-low group. Running performance on the treadmill, performance at lactate threshold, and ventilatory threshold improved in 60% of the live-high group and 20% of the live-low group. VO2max and maximum power were not different between the groups after the two-week period. Two weeks of live-high/train-low experience did not affect gross physiological parameters, but there was a slight effect on running performance and effect on well-being in a majority of athletes. Implication: Live-high/train-low has been shown to affect some athletes in a positive manner. In this study, 60% of Ss were positively affected. When prescribing experiences of this nature, the effects on each individual should be monitored. Those who do not respond to the experience should be offered living and training opportunities that best suit their needs.